The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3847/1538-4357/accd73
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Intermittency of Particle Distribution in Relativistic Plasma Turbulence

Abstract: Relativistic magnetically dominated turbulence is an efficient engine for particle acceleration in a collisionless plasma. Ultrarelativistic particles accelerated by interactions with turbulent fluctuations form nonthermal power-law distribution functions in the momentum (or energy) space, f(γ)d γ ∝ γ −α d γ, where γ is the Lorenz factor. We argue that in addition to exhibiting non-Gaussian distributions over energies, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Since all the vector components of the electromagnetic field and particle momenta are preserved, it is expected to capture some essential nonlinear interactions existing in the 3D case. Previous numerical studies involving 2.5D and 3D runs seem to produce similar energy spectra of fields and particles (e.g., Zhdankin et al 2017Zhdankin et al , 2018Comisso & Sironi 2018Vega et al 2023).…”
Section: Numerical Resultsmentioning
confidence: 77%
See 4 more Smart Citations
“…Since all the vector components of the electromagnetic field and particle momenta are preserved, it is expected to capture some essential nonlinear interactions existing in the 3D case. Previous numerical studies involving 2.5D and 3D runs seem to produce similar energy spectra of fields and particles (e.g., Zhdankin et al 2017Zhdankin et al , 2018Comisso & Sironi 2018Vega et al 2023).…”
Section: Numerical Resultsmentioning
confidence: 77%
“…We found that in both cases of the large and small boxes, the resulting particle distribution functions are qualitatively the same; they are well approximated by a universal log-normal distribution. This is in contrast with particle acceleration in weak guide-field turbulence, where energetic particles develop power-law energy distribution functions (e.g., Comisso & Sironi 2019;Zhdankin et al 2019;Wong et al 2020;Vega et al 2022bVega et al , 2023, which may indicate different acceleration mechanisms in these two cases.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations